Строение и функции мышц ротового аппарата и конечностей обыкновенного паутинного клеща Tetranychus urticae С. L. Koch (Trombidiformes, Tetranychoidea) - Акимов, И.А.; Ястребцов, А.В. (Вестник зоологии, 1981)
Morphology and functions of muscles of Tetranychus urticae C. L. Koch . mouth organs and legs I are described. Chelicerae (stylofor) protractor muscles previously unknown in T. urticae are found and a supposition on their origin is advanced. It is shown that chelicerae protraction and perforation plant tissue is realized by different muscles at three successive stages, protraction being initiated by contraction of the found protractor muscles. Then stylifer moves forwards forced by hydraulic pressure inside the body and plant perforation occurs due to contraction of the stylet muscles.